Pengaruh Literasi Keuangan dan Pengelolaan Keuangan Terhadap Kinerja dan Keberlangsungan UMKM di Kota Padang - Desiyanti, Rika; Chrismondari, Chrismondari; Romero, Adnan Raja (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2023)
The study aims to analyze the impact of financial literacy and financial management on the performance and sustainability of micro, small, and medium enterprises (MSMEs) in Padang City. This research is quantitative, and it uses primary data obtained through questionnaires. This research population is an MSMEs perpetrator in the city. Sampling techniques in research use census techniques. Around 150 people participated in the event. The data was processed with SPSS software for Windows version 22. The results of this study indicate that financial literacy has a positive impact on the performance of MSMEs and business sustainability; financial management has positive experience with the sustainability of enterprises; and financial management is consistent with the outcomes of MSMEs.